UPAYA GURU BIMBINGAN KONSELING DALAM MENGATASI CIRCLE TOXIC FRIENDSHIP DI SMKN 2 BUKITTINGGI - Luthvita Crishanti Sausan; Alfi Rahmi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research focuses on the efforts of guidance and counseling teachers to overcome toxic friendship circles, namely students who have problems with social relationships, so they cannot differentiate between friendships that have a good and bad impact on the students. Therefore, guidance and counseling teachers can identify and intervene in toxic friendship circles, with these two strategies. The research methodology used is descriptive qualitative, to describe the efforts of guidance and counseling teachers in overcoming toxic friendship circles. This research uses data collection techniques with interviews and documentation obtained from key informants, namely guidance and counseling teachers who teach in class XI accounting and class homeroom teacher of the student. The data analysis technique that the researcher used was data reduction, data display, data verification, while the validity of the data that the researcher used was data triangulation. The results from the researchers showed that the efforts made by guidance and counseling teachers to overcome toxic friendship circles for students at SMKN 2 Bukittinggi were by intervention and assistance in the implementation of counseling, namely the implementation of individual counseling, group guidance, group counseling, information services, and classical guidance, with the implementation of counseling, there is an evaluation and follow-up carried out by the counseling guidance teacher so that the results obtained and achieved by students can be known.